Evaluation of the Effects of Human Beta-Interferon Scaffold Attachment Region (IFN-SAR) on Expression of Vascular Endothelial Growth Factor-Fc (VEGF-Fc) Fusion Protein Expression in Chinese Hamster Ovary (CHO) Cells - Ehsan Naghneh; Es'hagh Pourmaleki; Azam Rahimpour (Tabriz University of Medical Sciences, 2020)
Background: Recombinant anti-vascular endothelial growth factor (VEGF) monoclonal antibodies and Fc-fusion proteins have been widely used for the effective treatment of retinal neovascular diseases. In this regard, VEGFR-Fc fusions, which act as strong VEGF inhibitors, have been approved for the treatment of age-related macular degeneration (AMD) and diabetic macular edema (DME). Production of monoclonal antibodies and Fc-fusion proteins relies on mammalian host systems such as Chinese hamster ovary (CHO) cells. Application of genomic regulatory elements including scaffold/matrix attachment regions (SAR/MARs) can profoundly affect recombinant protein expression in CHO cells. Methods: To construct the VEGFR-Fc expression vectors, the enhanced green fluorescent protein (EGFP) gene was replaced by the VEGFR-Fc coding sequence in pEGFP-SAR-puro and pEGFP-puro vectors. Recombinant plasmids were transfected to CHO-K1 cells using TurboFect transfection reagent. VEGFR-Fc expression was evaluated in transiently transfected cells as well as stable cell pools and clones using an enzyme-linked immunosorbent assay (ELISA). Results: IFN-SAR showed no significant effect on transient expression of VEGFR-Fc during 72 h of culture. However, a 2.2-fold enhancement in VEGFR-Fc fusion protein titer was observed in IFN-SAR containing stable cell pools. Further evaluation of the VEGFR-Fc expression level in single-cell clones also indicated that clones with the highest VEGFR-Fc expression belonged to the pools transfected with IFN-SAR construct. Conclusion: Our results indicate that the incorporation of IFN-SAR in expression vector can increase the expression of VEGFR-Fc in stable cell pools as well as single-cell clones. In contrast, transient expression of the fusion protein was not affected by IFN-SAR. More studies are needed to investigate the mechanism underlying this effect, including the analysis of mRNA expression and gene copy number in stable cell pools as well as clonal cells.